Edukasi Literasi Digital Marketing Bagi Pelaku UMKM di Pasar Sentral Medan - Irma Christiana; Chinta Felsya Fransisca; Alyssia Putri Manurung; Septia Mayang Saputri; Diah Ayu Zahra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
The aim of this activity is to enhance knowledge and skills in digital marketing and e-commerce for micro, small and medium enterprises in an effort to increase their sales and profits. The methods used in this activity include: explanations, sharing and discussion experiences, as well as direct practice of creating a Shopee account and how to make it attractive to buyers. The object is the